A Multi-Phase Study of Processing Depth: Attentional Mechanisms Underlying Effective Vocabulary Consolidation - Laaribi, Manal (JOLLT Journal of Languages and Language Teaching, 2026)
Processing depth is multidimensional; its definition must not overlook the complex cognitive and affective processes involved and their influence in operating memory performance. A clarified account of the mechanisms driving processing depth is needed to extend its application in cognition and language learning. This understanding could provide insights into the effectiveness of language teaching materials and vocabulary learning strategies over others. To serve this purpose, this study investigated the effect of different types of processing depth on vocabulary consolidation, both structural and semantic. Specifically, this study used a mixed-methods approach with a sample of 167 students and progressed through three phases, each building on insights gained from the previous one. The first within-subjects experiment investigated the effect of structural processing and two types of semantic processing on vocabulary consolidation among participants, while semantic outputs produced during the different types of processing were examined to understand the governing principles behind each type. It was revealed that semantic processing was more effective, with distinctiveness particularly associated with improved performance. Building on these findings, the second between-subjects experiment was designed to examine strategy training using vocabulary consolidation strategies reflecting different processing types, complemented by post-training feedback. The third phase focused on model building, developing the Attentive Depth of Processing Model; it posits that attention serves as a pivotal axis around which depth orbits, governed by attentional principles that support long-term consolidation. Overall, this study seeks to understand deep processing principles and provide a basis to improve vocabulary acquisition.